2013
DOI: 10.2190/ag.77.1.c
|View full text |Cite
|
Sign up to set email alerts
|

The Old, Old-Old, and the Oldest Old: Continuation or Distinct Categories? An Examination of the Relationship between Age and Changes in Health, Function, and Wellbeing

Abstract: This study aims to examine whether old age, old-old age, and oldest-old age comprise distinct categories via comparing persons aged 75-84, 85-94, and 95+ on demographics, health, function, and wellbeing. The sample was drawn from a representative longitudinal cohort of older persons in Israel. Matched cohort comparisons found a significant decline in Activities of Daily Living (ADL), instrumental ADL, cognitive function, percent of participants who go outside their home, and physical activity, with an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 48 publications
(56 reference statements)
3
57
0
3
Order By: Relevance
“…Due to increasing longevity, some authors have suggested an even more detailed division into three distinct groups in the fourth age: old (75-84), old-old (85-95), and oldest-old (95+) (Cohen-Mansfield et al 2013).…”
Section: A Rationale For Examining the Etiology Of Ageism In Differenmentioning
confidence: 99%
“…Due to increasing longevity, some authors have suggested an even more detailed division into three distinct groups in the fourth age: old (75-84), old-old (85-95), and oldest-old (95+) (Cohen-Mansfield et al 2013).…”
Section: A Rationale For Examining the Etiology Of Ageism In Differenmentioning
confidence: 99%
“…For example, discernible physical ability, social activity, and health declines are experienced throughout late adulthood (Berlau, Corrada, & Kawas, 2009;Buono, Urciuoli, & De Leo, 1998;Cohen-Mansfield et al, 2013;Talbot, Metter, & Fleg, 2000;Verbrugge, Gruber-Baldini, & Fozard, 1996). Also, in comparison to adolescents, older adults are more likely to have social controls such as marriage or children (and grandchildren) that inhibit criminal involvement (He, Sengupta, Velkoff, & DeBarros, 2005;Smith & Drew, 2002;Stelle, Fruhauf, Orel, & Landry-Meyer, 2010;Tamborini, 2007).…”
Section: Offending In Late Lifementioning
confidence: 99%
“…However, with increasing life expectancy, the traditional definition for an elderly population has become too heterogeneous, and a more detailed classification is needed. Recently, elderly patients were sub-divided into three life-stage groups: the young-old (aged 65–74), the middle-old (aged 75–84), and the old-old (aged over age 85) [2]. …”
Section: Introductionmentioning
confidence: 99%